(untitled) (Research, Society and Development, 2022)
Introduction: Seckel syndrome (SCKL) is a heterogeneous autosomal recessive disorder, the major characteristic of which is microcephalic osteodysplastic dwarfism, which is defined as severe intrauterine growth retardation, severe short stature, severe microcephaly, bird-like profile, retroverted chin and forehead, prominent nose, mental retardation and other congenital anomalies. Objective: Evaluate the therapeutic effect of proprioceptive neuromuscular facilitation/Kabat method (PNF/KM) for functional recovery in SCKL. Methods: A pre-treatment evaluation was performed, followed by an intervention involving PNF/KM. Sessions were held twice a week for ten weeks (total: 20 sessions), followed by a post-treatment evaluation. The evaluator and the therapist were blinded. The assessment instruments were Lawton & Brody’s Activities of Daily Living (ADL) Scale, Disabilities of Arm, Shoulder and Hand (DASH), Short Physical Performance Battery, Timed Up and Go test and upper limb muscle strength using a digital dynamometer. Results: No significant changes were found regarding ADL Scale or DASH. However, functional gains were achieved in activities that require biomechanical and proprioceptive actions of the shoulder, arm and wrist. Regarding the Short Physical Performance Battery, improvement was found in variables that require stabilization, strength, balance and agility. An improvement was found in the execution speed of the Timed Up and Go test. An improvement in muscle strength was following the intervention. Conclusion: This study showed that the PNF/KM method was not able to improve the performance on activities of daily living, but improvements were found with regards to balance, stabilization, strength and agility of the upper limbs and lower limbs.